Modernist Discourse Techniques in Rereading the Prophetic Sunnah - Al Shawali, Azzouz Ibin Omar (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2021)
The Sunnah of the Prophet has been vulnerable to modernist readings. Among the most well-known modernist readings are hermeneutical, structuralist, poststructuralist, interpretive, and reception. Modernist readings in this context are basically creative readings that position revelation under the rule of reason, aiming to deconstruct the religious text and putting rational and positivist thinking as an alternative to it. Most of these readings were individual or experimental attempts that did not produce tangible results in reality. Some have addressed the Sunnah of the Prophet in works that seem like reading projects aimed at popularizing the modernist vision, and at moving towards a modernist alternative that saves - in their view - contemporary Arab thought from the impact of traditional Islamic religious readings. This study attempts to discuss critically the most important of these projects, namely: Readings of Applied Islamisms (Mohammed Arkoun); Phenomenological Reading of Islamic Sciences (Hasan Hanafi); and An Epistemological Philosophical Reading (Muhammad Abid al-Jabiri).